Quest for a Christian America The Disciples of Christ and American Society to 1866 - Harrell, David Edwin (Social History of the Disciples of Christ, 1966)
The Disciples of Christ, led by reformers such as Alexander Campbell and Barton W. Stone, was one of a number of early-19th-century primitivist religious movements seeking to "restore the ancient order of things." The Disciples movement was little more than a loose collection of independent congregations until the middle of the 19th century, but by 1900 three clear groupings of churches had appeared. Today, more than 5 million Americans-members of the modern-day Disciples of Christ (Christian Church), Independent Christian Churches, and Churches of Christ, among others-trace their religious heritage to this "Restoration Movement."